Pengaruh Penggunaan Powerpoint Terhadap Hasil Belajar Pembelajaran Tematik Siswa Kelas IV SD Harapan 1 Medan - Abdi Karya Angelus Kacaribu; Regina Fredika Sipayung (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
This study aims to analyse the effect of using powerpoint on thematic learning outcomes of fourth grade students of SD Harapan 1 Medan with a research method in the form of an experiment in the form of a quasi experimental design. The research population of class IV A students totalled 27 students and class IV B students totalled 27 students. Data collection techniques used in the form of measurement techniques and data collection tools in the form of essay-shaped tests as many as 12 questions. In line with data analysis, the average final test of the experimental class was 65.34 and the control class was 53.7. The results of the t-test hypothesis test obtained tcount 7.86 while dk (27+27-2 =52) with the level (α = 5%) obtained ttable 0.68 means tcount>ttable. So that Ha is accepted. So according to the results of the calculation of effect size (ES), the value of ES = 1.85 is obtained, which means that the application of powerpoint in thematic learning affects the learning outcomes of fourth grade students of SD Swasta Harapan Medan by 96%.